Implications of Foliar Particulate Matter Deposition on the Physiology and Nutrient Allocation of Dominant Perennial Species of the Indo-Gangetic Plains - Singh, Harshita; Singh, Pallavi; Agrawal, Shashi Bhushan; Agrawal, Madhoolika (Frontiers in Plant Science, 2022)
The ramifications of different concentrations of foliar particulate matter on the physiology, nutrient stoichiometry, allocation pattern and their corresponding re-translocation rates were investigated for evergreen (Mangifera indica and Psidium guajava), semi-evergreen (Ficus religiosa and Azadirachta indica) and deciduous (Dalbergia sissoo) tree species in a simulation experiment over an exposure period of two years. Physiological parameters (Pn, gs, Ci, E and WUE), nutrient stoichiometry (C: N) in different plant parts and their allocation pattern for 5 macro- (C, N, K, Mg, Ca) and 5 (Zn, Ni, Mn, Cu, Fe) micro-elements at two different concentrations of particulate matter (ambient and elevated) with respect to control (no particulate load) were assessed. Significant differences in nutrient concentrations and their re-translocation rates were observed between the treatments in evergreen species compared to deciduous species. The photosynthetic rate significantly declined with an increase in foliar deposition of particulate matter. Higher variations in C, N, K, Mg and Zn levels were found compared to other elements under particulate matter stress and the ratio of C/N showed slight decline in mature leaves except in deciduous tree species. The nutrient stoichiometry revealed that the deciduous species were more tolerant whereas the retranslocation efficiency was maximum for the semi-evergreen tree species. The nutrient allocation was found greater in foliage compared to branch in evergreen and was opposite in semi-evergreen and deciduous tree species. The element re-translocation rate indicated an inconsistent behavior in nutrient recycling under the particulate matter load depending upon the tree species. The study entrenched a critical change in nutrient re-translocation and allocation pattern under the particulate stress in different parts of the tree, suggesting a novel approach for screening the tree species for sustainable plantation and planning of urban areas.